THE IMPACT OF COVID-19 PANDEMIC ON LEARNING IN INDONESIA - Agustin Kurniawati (Jurnal MEKOM (Media Komunikasi Pendidikan Kejuruan), 2021)
COVID-19 has serious impacts on various sectors, including educational system. This writing aims to see the impact of the Covid-19 pandemic on learning in Indonesia. As for the background of this writing because how Covid-19 pandemic has a tremendous impact on education, such as learning methods, students’ achievement, and teachers’ struggles. Many schools around the world are closed to stop the spreading of Covid-19 virus. Even though there is a pandemic, the learning process must run smoothly so that education does not go out. With the help of the internet, online learning will be easier to do even though there are still some obstacles in its implementation. The government has begun to decide to implement a policy to close schools and begin to apply learning methods with an online system (from home). However, this has several impacts for students as well for teachers. Therefore, there must be some efforts or solutions to solve the problems for the educational system as well as new learning methods.